Electronic Module Development with Project Based Learning in Web Programming Courses - Prasetya, Agus; Muqorobin, Muqorobin (International Journal of Computer and Information System (IJCIS), 2021)
In this era of the Covid-19 pandemic, students are getting used to online learning or daring. In supporting online teaching and learning activities, electronic modules have been developed so that the learning system can run in two directions and be more interesting. For this reason, this study aims to (1) Design and implement the development of electronic modules based on learning projects in Web programming courses at ITB AAS Indonesia. (2) To find out student responses to the development of project-based e-modules based on Web programming courses at ITB AAS Indonesia. This study uses research and development methods. with the development of the ADDIE model. To determine student responses to the electronic module, the researcher uses questionnaires. The results of the study show that: 1) The results of the design and implementation of e-modules that have been developed on web programming courses that use learning project-based learning models can be applied. 2) The results of the percentage of students who gave a very good response really good were 58,1%, good 22,5% %, sufficientt 19,4% and there were no students who gave less, or very less responses.